Interdigitating dendritic cell sarcoma located in the adrenal gland: a case report and literature review - Peng Hao (SAGE Publishing, 2021)
We report a case of interdigitating dendritic cell sarcoma (IDCS) originating from the adrenal gland. A 57-year-old middle-aged woman with no previous history of malignancy came to our hospital after color Doppler ultrasound revealed a right adrenal mass. An abdominal computed tomography scan also showed an adrenal mass. Postoperative pathology confirmed the diagnosis of IDCS. After complete surgical removal of the adrenal tumor, the patient has been disease-free for 1 year. IDCS may have a good prognosis after surgical resection. To our knowledge, this is only the second reported case of IDCS in the adrenal region.